Menjawab Tuduhan Comma Johanneum 1 Yohanes 5:7-8 Sebagai Ayat Palsu Melalui Tulisan Bapa-Bapa Gereja - Didit Yuliantono Adi; Yohanes Twintarto Agus Indratno (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
The idea for writing this scientific work came from the author's ministry experience, which often encountered questions about the inerrancy of the Bible, especially regarding the authenticity of 1 John 5:7-8 or the Comma Johanneum. The purpose of writing this scientific work is to find evidence that 1 John 5:7-8 is the Word of God revealed to the apostle John. The method used in this writing is a qualitative method with a literature study approach. From this research, evidence was found that, although the Comma Johanneum is not found in ancient Greek texts, this verse can be traced to an ancient Latin document called the Vetus Latina and from the writings of the church fathers, namely Tertullian, Ciprian, Athanasius, Origen, Augustine , Pricilian, Jerome, Gregory Nazianus and Johanes Chrisostomos whose writings still exist and have been preserved to this day. Thus the accusation that this verse is fake or a hoax has been successfully refuted.